Houdini and me - Gutman, Dan (Holiday House, 2021)
Eleven-year-old Harry Mancini lives in the house where Houdini spent his final years, so he has always been interested in the famous magician, and has even learned a few simple magic tricks; he just never expected Houdini to contact him from beyond the grave--and what Houdini wants him to do could well cost Harry his own life.